Correlation of heart rate recovery and heart rate variability with atrial fibrillation progression. Issue 11 (November 2021) - Yoon, Gwang-Seok; Choi, Seong-Huan; Kwon, Sung Woo; Park, Sang-Don; Shin, Sung-Hee; Woo, Seong-Ill; Kwan, Jun; Kim, Dae-Hyeok; Baek, Yong-Soo
Objective: To examine the combination of heart rate recovery (HRR) and heart rate variability (HRV) in predicting atrial fibrillation (AF) progression. Methods: Data from patients with a first detected episode of AF who underwent treadmill exercise testing and 24-h Holter electrocardiography were retrospectively analysed. Autonomic dysfunction was verified using HRR values. Sympathetic and parasympathetic modulation was analysed by HRV. AF progression was defined as transition from the first detected paroxysmal episode to persistent/permanent AF. Results: Of 306 patients, mean LF/HF ratio and HRR did not differ significantly by AF progression regardless of age (< or ≥65 years). However, when the LF/HF ratio was divided into tertiles, in patients aged <65 years, the mid LF/HF (1.60–2.40) ratio was significantly associated with lower AF progression rates and longer maintenance of normal sinus rhythm. For patients aged <65 years, less metabolic equivalents were related to higher AF progression rates. For patients aged ≥65 years, a low HRR was associated with high AF progression rates. Conclusion: In relatively younger age, high physical capacity and balanced autonomic nervous system regulation are important predictors of AF progression. Evaluation of autonomic function assessed by age could predict AF progression.